2022
DOI: 10.3389/fpls.2022.822340
|View full text |Cite
|
Sign up to set email alerts
|

MrMYB44-Like Negatively Regulates Anthocyanin Biosynthesis and Causes Spring Leaf Color of Malus ‘Radiant’ to Fade From Red to Green

Abstract: The “Spring-red-leaf” crabapple cultivar has young red leaves and mature green leaves. However, the mechanism of anthocyanin biosynthesis in crabapple leaves in spring remains unknown. In this study, Illumina RNA sequencing (RNA-Seq) was performed on Malus ‘Radiant’ leaf tissues in different stages of development. Twenty-two genes in the anthocyanin biosynthesis pathway and 44 MYB transcription factors (TFs) were significantly enriched among differentially expressed genes (DEGs). Three R2R3-MYB TFs in subgroup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 42 publications
0
14
0
1
Order By: Relevance
“…For example, Tang et al reported that the anthocyanin content gradually decreases during red fading in herbaceous peony leaves [ 1 ]. Decreasing anthocyanin content led to fading red color in Malus ‘Radiant’ leaves [ 2 ]. Flavonols, another subgroup of flavonoids, can also modulate plant organ color as co-pigments of anthocyanins [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Tang et al reported that the anthocyanin content gradually decreases during red fading in herbaceous peony leaves [ 1 ]. Decreasing anthocyanin content led to fading red color in Malus ‘Radiant’ leaves [ 2 ]. Flavonols, another subgroup of flavonoids, can also modulate plant organ color as co-pigments of anthocyanins [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The bimolecular fluorescence complementation (BiFC) assays were performed as described in previous reports (Meng et al ., 2022). MsMYB10 and MsMYB62‐like were amplified and inserted into the pSPYNE‐35S vector, whereas MsbHLH3 was amplified and inserted into the pSPYCE‐35S vector (Walter et al ., 2004).…”
Section: Methodsmentioning
confidence: 99%
“…domestica ‘Fuji’ fruit or M . spectabilis leaves were described previously (Hu et al ., 2022; Meng et al ., 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extraction of phenolic compounds was described previously [ 8 , 47 ]. The extraction supernatant was absorbed and filtered through a 0.45 µm filter, which was analyzed by HPLC coupled with a diode array detector (DAD) (Shimadzu LC-2030C Liquid Chromatograph, Shimadzu, Kyoto, Japan; Inertsil C-18 column, 5.0 µm particle size, 4.6 mm × 250 mm).…”
Section: Methodsmentioning
confidence: 99%